A phase II/III randomized clinical trial of CisPlatin plUs Gemcitabine and Nabpaclitaxel (GAP) as pReoperative chemotherapy versus immediate resection in patIents with resecTable BiliarY Tract Cancers (BTC) at high risk for recurrence: PURITY study - Niger, Monica; Nichetti, Federico; Fornaro, Lorenzo; Pircher, Chiara; Morano, Federica; Palermo, Federica; Rimassa, Lorenza; Pressiani, Tiziana; Berardi, Rossana; Gardini, Andrea Casadei; Sperti, Elisa; Salvatore, Lisa; et al. (BMC cancer, 2024)
Biliary tract cancers (BTCs) are rare and lethal cancers, with a 5-year survival inferior to 20%(1-3). The only potential curative treatment is surgical resection. However, despite complex surgical procedures that have a remarkable risk of postoperative morbidity and mortality, the 5-year survival rate after radical surgery (R0) is 20-40% and recurrence rates are up to ~ 75%(4-6). Up to ~ 40% of patients relapse within 12 months after resection, and half of these patient will recur systemically(4-6). There is no standard of care for neoadjuvant chemotherapy (NAC) in resectable BTC, but retrospective reports suggest its potential benefit (7, 8).
Online veröffentlicht: 8. April 2024
Gesehen am 06.11.2024